2004
DOI: 10.1145/1035334.1035352
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic regimes and approximations for discriminatory processor sharing

Abstract: We study the joint queue length distribution of the Discriminatory Processor Sharing model, assuming all classes have phase-type service requirement distributions. We show that the moments of the joint queue length distribution can be obtained by solving linear equations. We use this to study the system in two asymptotic regimes. In the first regime, the different user classes operate on strictly separated time scales. Then we study the system in heavy traffic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…After developing a procedure to determine all moments of the queue length distributions from systems of linear equations, [26] show that the variability of the queue length vector is of a lower order than the mean queue lengths, which directly leads to state space collapse of the multi-dimensional queue length process. In [22] it was indicated that a similar approach as in [26] could be followed for the heavy-traffic analysis of the DPS queue with phase-type distributions. Here we follow a different and more direct approach, by investigating the joint probability generating function of the queue lengths.…”
Section: Introductionmentioning
confidence: 99%
“…After developing a procedure to determine all moments of the queue length distributions from systems of linear equations, [26] show that the variability of the queue length vector is of a lower order than the mean queue lengths, which directly leads to state space collapse of the multi-dimensional queue length process. In [22] it was indicated that a similar approach as in [26] could be followed for the heavy-traffic analysis of the DPS queue with phase-type distributions. Here we follow a different and more direct approach, by investigating the joint probability generating function of the queue lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Rege and Sengupta [19] obtained the moments of the queue length distributions as the solutions to linear equations for the case of exponential service requirements, and they also proved a heavytraffic limit theorem for the joint queue length distribution. These results were extended to phase type distributions by van Kessel et al [13]. Kim and Kim [15] found the moments of the sojourn time in the M/M/1 DPS queue as a solution of linear simultaneous equations.…”
Section: Introductionmentioning
confidence: 67%
“…The sensitivity increases when ρ = 0.5, but still remains limited. For ρ = 0.75, however, the sensitivity is considerably amplified, and becomes even stronger for ρ = 0.9 and ρ = 0.95 [19]. Evidently, for w ≈ 1, the strict insensitivity to the service requirement distribution of the ordinary multi-class PS system manifests itself, regardless of the load.…”
Section: Sensitivity To the Service Requirement Distributionmentioning
confidence: 94%
“…First we consider a relatively lightly-loaded system (ρ = 0.25; Tables I-V), and then repeat the experiment for a more heavily-loaded system (ρ = 0.75; Tables VI-X). For ρ = 0.5, ρ = 0.9 and ρ = 0.95, we refer to [19].…”
Section: Sensitivity To the Service Requirement Distributionmentioning
confidence: 99%